Criminal Sanctions for Juvenile Bullying Offenders Resulting in Fatalities: An Analysis under Indonesia’s Juvenile Criminal Justice System Law No. 11 of 2012 - Eer Herawati; Muhammad Chotib; Abu Nawas (UIN Jakarta, 2026)
The phenomenon of bullying among adolescents in Indonesia has shown an increasingly alarming trend, particularly when such behavior escalates into acts of violence resulting in loss of life. This condition raises complex legal issues, especially regarding the criminal liability of children as perpetrators. On the one hand, children in conflict with the law must be afforded legal protection and rehabilitation; on the other hand, the severe consequences of their actions demand law enforcement that ensures justice for victims. This study aims to analyze the regulation and application of criminal sanctions against child perpetrators of bullying resulting in death within the perspective of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, as well as to examine its conformity with the principles of restorative justice. This research employs a normative juridical method using statutory, conceptual, and case approaches. The legal materials consist of primary legal sources in the form of legislation, secondary legal sources such as legal literature and scholarly opinions, and tertiary materials as supporting references. Data collection is conducted through library research, while the analysis is carried out qualitatively using legal interpretation and legal reasoning methods. The results of the study indicate that under Law Number 11 of 2012, child perpetrators of bullying can still be held criminally liable, particularly in cases resulting in death. However, the imposition of criminal sanctions must take into account the best interests of the child and prioritize restorative justice principles. In serious criminal offenses resulting in death, diversion mechanisms cannot be optimally applied due to the limitations related to the severity of criminal sanctions. Therefore, formal criminal proceedings remain necessary while still integrating child protection principles in their implementation. In conclusion, the imposition of criminal sanctions against child perpetrators of bullying resulting in death is necessary for the enforcement of the law; however, it must be carried out proportionally without disregarding restorative justice principles. A balance is required between protecting the child offender and ensuring justice for the victim to achieve fair and humane legal objectives. Keywords: Bullying, Child Offender, Criminal Liability, Restorative Justice, Juvenile Criminal Justice System